KARAKTERISTIK PENDERITA MIOMA UTERI RAWAT INAP DI RUMAH SAKIT TENTARA TK-IV 01.07.01 PEMATANGSIANTAR TAHUN 2014 - sheyna zein; Rahayu Lubis; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT Uterine myoma is a benign neoplasm on the myometrium layerconsists of cells of smooth muscle tissue and connective tissue fibroids which the literature also known as leiomyomas or fibroids. It the most common occurrence in women of childbearing age. In Indonesia, the proportion of myoma uterine 2.3% - 11.7% of all gynecological patientstreated. This study is aimed to determine the characteristics of patients with myoma uterine in the Tentara Tk-IV 01.07.01 Hospital Pematangsiantar 2014. Kind of this study is descriptive with case series design. Population and sample were 82 data patients (total sampling). Data was analyzed descriptively by using Chi-square and Fisher's Exact. The results showed the proportion of patients with uterine myoma highest in the age group 41-50 years 70.7%, Bataknese 55.4%, Senior High School 47.6%, Housewives 32.9%, Marriage 97.6%, Abnormal Bleeding 48.8%, Multiparities 46.3%, Not Pregnant 98.8%, Hemoglobin>12 g% (53.7%), Intramural myomas type (47.6%), Total Hysterectomy (58.5%), Average Lenght of Stay 6 days. The results of test statistically were not significant differences age based on the type of myoma uterine (p=0.547), age based on the main complaints (p = 0.900), occupationbased on the main complaints (p=0.936), type of myoma uterine based on parity (p=0.478), The main complaintbased on parity (p = 0.709), hemoglobin levels based on the type of myoma uterine (p=0.116), treatment based on the type of uterine myoma (p=0.762). Expected to women who have risk factors for the occurrence of uterine myoma, especially women aged 41-50 years and who frequently gave birth (multiparity) in order to be bette to maintain their health with healthy diet and regular check-up for early detection of the possibility of the discovery uterine myoma. To Tentara HospitalTk-IV 01.07.01 recommended to complementary recording medical records which related uterine myoma such as age of menarche.